Amorfino y su resignificación turística, cantón Salitre, Provincia del Guayas - Moran Suarez, Viviana Isabel (2019)
The research analyses, promotes and disseminates the message of the Amorfino of The Canton Salitre, Province of Guayas, in order to awaken the interest of young people in knowing in orden from them to know their ancestral roots, customs, traditions, the history of how it originated amorfino as a Montubian orality, the changes that had to be given to the knowledge gained by the conquerors of Ecuador for the transformation and adoption of the settlers who were settled along the Littoral region to create their own cultural identity, strengthen their sense of belonging as time goes on and leave it as a legacy to their parents. Acculturation plays a very important role in the conservation of this intangible heritage property of the canton Salitre, it is about raising awareness of people in practicing their culture, the activities carried out together with the community, celebrating the dates and increase cultural tourism, history, experiential tourism and dissemination. The message of amorfino is being analyzed in order to determined its tourist resignificance because the inhabitants of this town are aware of the change that this unprecedented and characteristic manifestation of them has had, they need to change their mentality, promote the dialogue cuts and essential amorfino through events that are constantly organized on representative dates for the influx of tourists and, in this way, the community benefits economically and strengthens its sense of belonging to development Tourist